The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.iecr.8b00379
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Formation and Subsequent Air Entrainment inside a Liquid Pool

Abstract: The origins of free surface vortex and gas entrainment are investigated within a liquid pool using a rotating cylindrical disc having longitudinal axis normal to the gas–liquid interface with varying submergence from 1.40 to 2.85 times the disc radius (20 mm). A generalized vortex profile is obtained by suitable scaling for a range of rotational Froude numbers (2.38–11.18). The transient evolution rate of the vortex tip followed logarithmic law and is correlated with experimental data of air and glycerin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Again, in the same year, they examined the pattern of air filaments in symmetric converging fields by considering the same gas–liquid pair. Kumar et al attempted experimentally to elucidate the interfacial vortex and air penetration caused by an immersed rotary flat circular disc under a liquid bath with the depth of submergence and also predicted the asymmetric structured cusp with the aid of a tilted disc (0–17.45°). In addition to that, Prajapati et el .…”
Section: Introductionmentioning
confidence: 99%
“…Again, in the same year, they examined the pattern of air filaments in symmetric converging fields by considering the same gas–liquid pair. Kumar et al attempted experimentally to elucidate the interfacial vortex and air penetration caused by an immersed rotary flat circular disc under a liquid bath with the depth of submergence and also predicted the asymmetric structured cusp with the aid of a tilted disc (0–17.45°). In addition to that, Prajapati et el .…”
Section: Introductionmentioning
confidence: 99%
“…Observations of such a kind of cusp profiles are quite important and relevant to describe the fluidic pattern around the spinning roller in the present investigation. Numerous researchers ,,,,,, attempted to characterize the gaseous cusp profile thoroughly to extract the underlying physics in their studies. Figure illustrates the pattern of radial distance of the cusp from the center of the roller by considering the variation of S / D and Ca .…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that a thicker film and longer cusp are obtained in a highly viscous pool. Kumar et al performed experiments to obtain free surface vortex (FSV) entrainment in the bath using a swirling disk. They revealed the dependence of the vortex profile on the tangential velocity (measured by the Froude number, ) and depth of immersion of the disk.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that bathtub vortices which form under experimental conditions contain a vortex core where vorticity is non-negligible, resulting from the fluid's viscosity [20,116]. Many authors in the literature have studied this type of fluid flow; for example see [5,6,113] for experimental studies, [33,77,182] for numerical studies and [77,138,192] for analytical studies. Since most of our theoretical discussion has been centred on rotating fluids in shallow water, we will be interested in the component of vorticity which is perpendicular to the free surface.…”
Section: Chapter 5 Vorticitymentioning
confidence: 99%